1998
DOI: 10.1161/01.cir.97.3.237
|View full text |Cite
|
Sign up to set email alerts
|

5-Methyltetrahydrofolate, the Active Form of Folic Acid, Restores Endothelial Function in Familial Hypercholesterolemia

Abstract: Background-Impaired nitric oxide (NO) activity is an early event in the pathogenesis of cardiovascular disease, resulting from either reduced NO formation or increased NO degradation. Administration of tetrahydrobiopterin (BH 4 ), an essential cofactor for NO production, could restore NO activity in familial hypercholesterolemia (FH). Because folates have been suggested to stimulate endogenous BH 4 regeneration, we hypothesized that administration of 5-methyltetrahydrofolate (5-MTHF, the active circulating for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
240
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(248 citation statements)
references
References 34 publications
5
240
0
3
Order By: Relevance
“…There has been recent interest in a potential antioxidant role for folate independent of its homocysteine-lowering effect. This has been demonstrated in experimental systems in vitro (Usui et al, 1999), and at a very high concentration in vivo (Wilmink et al, 2000;Verhaar et al, 1998;Nakano et al, 2002). There is no evidence from this study that physiological intakes of folate have a measurable antioxidant effect in vivo.…”
Section: Effect On Antioxidant Activitymentioning
confidence: 54%
“…There has been recent interest in a potential antioxidant role for folate independent of its homocysteine-lowering effect. This has been demonstrated in experimental systems in vitro (Usui et al, 1999), and at a very high concentration in vivo (Wilmink et al, 2000;Verhaar et al, 1998;Nakano et al, 2002). There is no evidence from this study that physiological intakes of folate have a measurable antioxidant effect in vivo.…”
Section: Effect On Antioxidant Activitymentioning
confidence: 54%
“…Oral folic acid supplementation has been shown to improve brachial artery endothelial function in subjects with hyperhomocysteinemia, 11,12 familial hypercholesterolemia, 13,14 and coronary artery disease. [7][8][9][10] However, when we started our study, there was limited information in subjects with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]6 We and others have demonstrated that folic acid can significantly improve endothelium-dependent vasodilation in patients with coronary artery disease, [7][8][9][10] asymptomatic hyperhomocysteinemia, 11,12 and asymptomatic familial hypercholesterolemia. 13,14 While this benefit may in part be related to homocysteinelowering, 7,8 other studies suggest that the restoration of endothelial function by folates may be independent of its homocysteine-lowering effect. 10,14 In fact, 5-methyltetrahydrofolate, the active metabolite of folic acid, may have direct effects on uncoupled eNOS, which results in increased release of NO and decreased release of superoxide anion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] The protective effect of these B vitamins may be partly explained by mechanisms independent of Hcy, as suggested by several recent studies, 25 and the B vitamins may themselves affect BP. 26,27 Observations that Hcylowering therapies with folic acid-based treatments have been followed by decreases in BP raise the possibility that the link between Hcy and BP is causal, which is important since Hcy levels can easily be lowered by folic acid-based regimens. 28 The purpose of this study was to determine the relationship of Hcy with BP, and other cardiovascular disease risk factors, including body mass index (BMI), glucose, lipids and smoking status on the one hand and between Hcy nutritional determinants and hypertension in a healthy adult Iranian population as part of the 'Tehran Homocysteine Survey' on the other hand (Table 1).…”
mentioning
confidence: 99%